2013
DOI: 10.1111/j.1525-1594.2012.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of Low‐Dose Bone Morphogenetic Protein‐2 Using Heparin‐Conjugated Fibrin in the Posterolateral Lumbar Fusion of Rabbits

Abstract: The heparin-conjugated fibrin (HCF) system has been developed to deliver bone morphogenetic proteins (BMPs) for a long-term period and thus enhance bone regeneration. In the present study, we tested the effectiveness of the delivery system for spinal fusion with a very low dose of BMP-2. A total of 15 rabbits underwent posterolateral lumbar spine, divided into three groups. The control group received only collagen sponges without BMP-2, another group (BMP-only group) received collagen sponges loaded with BMP-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The HCF complex can decrease the BMP dose while promoting effective bone formation, which may decrease the side effects associated with a high dose of BMP. Koo et al reported a poor result with 20 mg of rhBMP-2 but a good result with 100 mg of rhBMP-2 at each spinal level (4,5). In our study, we found a good fusion rate with 75 or 100 mg of rhBMP-2 at each level, similar to the results of Koo et al However, the optimal concentration of BMP may vary according to the animal model used.…”
Section: Discussionsupporting
confidence: 88%
“…The HCF complex can decrease the BMP dose while promoting effective bone formation, which may decrease the side effects associated with a high dose of BMP. Koo et al reported a poor result with 20 mg of rhBMP-2 but a good result with 100 mg of rhBMP-2 at each spinal level (4,5). In our study, we found a good fusion rate with 75 or 100 mg of rhBMP-2 at each level, similar to the results of Koo et al However, the optimal concentration of BMP may vary according to the animal model used.…”
Section: Discussionsupporting
confidence: 88%
“…However, the long-term side effects have not been tested, and in some cases, the use of heparin-loaded biomaterials has proven ineffective in vivo. 25 In addition, we have shown in a rat ectopic model that, while collagen sponges soaked with BMP2 and heparin did result in more bone formation compared to sponges soaked with BMP2 alone, the use of an HS variant, rather than heparin, improved bone formation even further. 26 We hypothesize that while heparin may enhance the retention/activity of BMP2 (or other GFs) under certain conditions, its binding “promiscuity” means that it may also inhibit other factors that play a role in the repair process, leading to suboptimal or deleterious results.…”
Section: Introductionmentioning
confidence: 91%
“…In 2002, the Federal Drug Administration (FDA) approved a device called INFUSE, which contained a porous resorbable collagen sponge to retain the BMP-2 [34], [35]. However, the open porous structure of the collagen carrier failed to reduce the dosage and some side effects of BMP-2.…”
Section: Discussionmentioning
confidence: 99%